Digital technology in national curricula: a dialogue among Iberoamerican countries - de Araújo, Allyson Carvalho; Xavier, Kesia da Silva; Moya-Mata, Irene; da Costa, Alan Queiroz; Canon-Buitrago, Edwin Alexander; de Oliveira, Braulio Nogueira; de Carvalho, Ricardo Souza (Frontiers in Sports and Active Living, 2024)
Introduction In today's world, digital technologies have become pervasive, impacting every aspect of our lives. Even in subjects such as Health and Physical Education (HPE), which traditionally emphasizes experiential, active, and corporeal learning, there is a growing interest in the role and influence of new technologies. These technologies not only have the potential to transform human movement and health cultures, but they also offer valuable tools to facilitate teachers' work and enhance student learning. Considering the context of the Research Network on Interactive Digital Didactic Materials, which includes researchers from Iberoamerican countries, this research examines how media and digital technologies are considered in the official Physical Education and curriculum documents from Brazil, Uruguay, Chile, Colombia, and Spain. Methods The research comprises a content analysis of official National Curricular Proposals of the selected countries. Considering the specificities of each country to publish their curricula policies, we selected eight different documents from five countries (Brazil, Uruguay, Spain, Colombia, and Chile). We looked for indicators expressed by terms such as “media,” “digital culture,” and “technology” in the documents, all of them related to Physical Education. Results The findings show arguments and proposals for using technology in Physical Education in all documents. However, the curricula trigger this theme in different forms, as an autonomous or transversal character integrated into subjects such as HPE. This fact may be highlighted by the goals of learning areas, which sometimes trigger teaching themes through technology. Discussion Under the Media-Education theory lens, we argue that there is no standard for educational investment in curricula in media and technology. Some documents point to the technology use dimension, while others point to the critical or productive dimension that technology makes possible. The literature highlights the need for an organic approach between these dimensions, and educators and policymakers are asked to rethink their curriculum proposals.